Legal Analysis of Land Use Rights (Case Study in Takalar Regency) - Rijal, Syamsul; Asriati, Asriati (eScience Humanity Journal, 2024)
This study aims to analyze the legal aspects related to land use rights in Takalar Regency. Land use rights are a form of right given to individuals or legal entities to utilize land that does not belong to them, with certain time and use restrictions regulated in the law. This study uses an empirical juridical approach, which combines the study of applicable laws and regulations with field data collected through interviews and observations. The results of the study show that there are several problems in the implementation of land use rights in Takalar Regency, such as the lack of public understanding of the regulations governing land use rights, as well as the overlap of land use that causes legal disputes. This study concludes that more intensive socialization from the government is needed and improvement of the supervision mechanism to avoid abuse of land use rights. Thus, this research is expected to contribute to efforts to improve the regulation and implementation of land use rights in Indonesia, especially in Takalar Regency.